Burden of tuberculosis and challenges related to screening and diagnosis in Ethiopia. (May 2020) - Mohammed, Hussen; Oljira, Lemessa; Roba, Kedir Teji; Ngadaya, Esther; Ajeme, Tigest; Haile, Tewodros; Kidane, Achenef; Manyazewal, Tsegahun; Fekadu, Abebaw; Yimer, Getnet
Abstract: Introduction: One-third of tuberculosis (TB) cases in Ethiopia are missing from care for reasons that are not well studied. The aim of this study was to assess TB burden and identify challenges related to TB screening and diagnosis in Ethiopia. Methods: A facility-based cross-sectional study was conducted in seven health facilities selected from two regions and two city administrations of Ethiopia using stratified random sampling procedures. The data of 1, 059, 065 patients were included from outpatient department, HIV clinic, diabetic, and maternal-child health clinics. Data were collected from October to December 2018 using a retrospective review of three years' facility data (2015 to 2017) supplemented by a semi-structured interview with purposively selected health care workers and heads of the health facilities. Results: A total of 1, 059, 065 patients visited the health facilities in three years, of these, 978, 480 (92.4%) were outpatients. Of the total, 20, 284 (2%) were presumptive TB cases (with 2 weeks or more cough), 12.2% (2483/20284) of which had TB. For the type of TB, 604 (24.3%) were smear-positive pulmonary TB (PTB), 789 (31.8%) were smear-negative PTB, 719 (29%) were extra-pulmonary TB, and data were missing for the rest. TB screening was integrated into HIV clinic, outpatient department, diabetic clinic but not with the maternal and child clinics. High patient load, weak TB laboratory specimen referral system, and shortage of TB diagnostic tools including Xpert MTB/RIF assay and chest X-ray, were the major challenges in the screening and diagnosis of TB. Conclusion: The burden of TB was high in the study setting, and frequent interruption of laboratory reagents and supplies hampered TB screening and diagnostic services. Realizing the END-TB strategy in such resource-limited settings requires sustainable TB diagnostic capacity and improved case detection mechanisms, with national TB programs strongly integrated into the general health care system.